2012
DOI: 10.1002/jms.3045
|View full text |Cite
|
Sign up to set email alerts
|

Free and bound aroma compounds characterization by GC‐MS of Negroamaro wine as affected by soil management

Abstract: Negroamaro is an autochthonous wine grape variety of Southern Italy, which is becoming very important for the Italian wine market. The wine aroma is primary affected by the chemical composition of grapes, which can be influenced also by agronomic practices such as soil management. In this study, the free and bound aroma characterization was performed by gas chromatography-mass spectrometry analyses, and the influence of two soil managements (cover cropping and soil tillage) was evaluated. A total of 40 volatil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 32 publications
4
34
0
2
Order By: Relevance
“…Moreover, Bureau and others () pointed out that C 13 ‐norisoprenoidic and phenolic glycosides levels decreased in shaded bunches. In contrast, Toci and others () did not find any obvious changes in the contents of glycoside compounds when regulating the water stress to study the influence of soil management, such as the cover cropping and soil tillage, on the wine aroma. Interestingly, Martínez‐Gil and others () sprayed oak extracts on grape leaves at different veraison times and found that the oak extracts could be assimilated and stored as glycosidic compounds in grapes.…”
Section: Grape Aroma Glycosidesmentioning
confidence: 91%
“…Moreover, Bureau and others () pointed out that C 13 ‐norisoprenoidic and phenolic glycosides levels decreased in shaded bunches. In contrast, Toci and others () did not find any obvious changes in the contents of glycoside compounds when regulating the water stress to study the influence of soil management, such as the cover cropping and soil tillage, on the wine aroma. Interestingly, Martínez‐Gil and others () sprayed oak extracts on grape leaves at different veraison times and found that the oak extracts could be assimilated and stored as glycosidic compounds in grapes.…”
Section: Grape Aroma Glycosidesmentioning
confidence: 91%
“…HS-SPME is a commonly employed sampling method for identification and analysis of volatile essential oils and aroma compounds in general (Toci et al, 2012), provided that the target compounds exhibit acceptable partitioning to the fibre. Hence, HS-SPME was chosen to study aroma-impact compounds in orange juice.…”
Section: Gc-o/fid and Heart-cut Multidimensional (H/c Mdgc-o/ms) Analmentioning
confidence: 99%
“…[16][17][18][19] Common methods used to study monoterpene glycosides perform enzymatic hydrolysis of the glycoside fraction, which was previously isolated by solid-phase extraction, and gas-chromatography coupled with mass spectrometry (GC-MS) analysis of the liberated aglycones. 9,20,21 Drawbacks of these indirect methods are the need of enzymes with a specific selectivity, which can lead to rearrangements and hydrolytic artifacts, as well as not providing information on the nature of the sugar residues. Recently, liquid chromatograph high-resolution MS (LC-HRMS) and multiple MS (MS/MS) methods to characterize these glycoside compounds in grape has been used.…”
Section: Introductionmentioning
confidence: 99%